Processes of care during a randomized trial of office-based treatment of opioid dependence in primary care. - Fiellin, David A; O'Connor, Patrick G; Chawarski, Marek; Schottenfeld, Richard S (The American journal on addictions / American Academy of Psychiatrists in Alcoholism and Addictions, 2004)
Improving office-based treatment of opioid dependence requires an evaluation of processes of care. We evaluated the care provided by physicians to opioid dependent patients during a trial of office-based methadone maintenance. We conducted chart audits and a focus group. Audits identified lapses in monitoring of urine toxicology results and paperwork completion. The focus group identified the logistics of dispensing, the receipt of urine toxicology results, difficulties arranging psychiatric services, communications with the opioid treatment program, and non-adherence to medication as problematic. Strategies to support logistical aspects of office-based care should be developed. Chart audits and mentoring should be considered as a mechanism to foster quality care. These processes of care are likely to require attention for treatment using methadone or buprenorphine.
Keywords: Adolescent; Adult; Female; Focus Groups; Humans; Male; Medical Audit; Methadone; Middle Aged; Multicenter Studies as Topic; Narcotics; Office Visits; Opioid-Related Disorders; Outcome and Process Assessment (Health Care); Primary Health Care; Process Assessment (Health Care); Quality Assurance, Health Care; Randomized Controlled Trials as Topic; Referral and Consultation; Substance Abuse Detection; Treatment Refusal; United States